Ethnic school segregation in Copenhagen: A step in the right direction?. (November 2019) - Nielsen, Rikke Skovgaard; Andersen, Hans Thor
The Danish school system is based on a general belief in the quality and merits of public schooling. Until 20 years ago, more than 90% of all children attended public school. However, this trend has recently seen a decline because of rising spatial inequalities; nowhere is this more visible than in the major cities, particularly Copenhagen. One visible change has been the rise in the number of children with non-Danish backgrounds in public schools in major cities. Previous studies of Copenhagen showed that, while the level of ethnic residential segregation was moderate, the level of school segregation was remarkably high. The purpose of this paper is to revisit the case of Copenhagen through: (a) quantitatively identifying the level of ethnic school segregation in Copenhagen and the change over the last decade, and (b) qualitatively analysing the considerations regarding the school choice of parents in an ethnically diverse district. The paper identifies decreasing levels of ethnic school segregation in public schools but a markedly higher and increasing level in private schools. The qualitative material points to still-existing concerns regarding specific public schools with high proportions of pupils of non-Danish backgrounds as well as to parents who choose to overlook such concerns and opt for the local public school.